Study on the Development of Secondary Vocational Education in China - Junfeng Fu (International Journal of Education and Humanities, 2023)
In order to understand the current situation of secondary vocational education research in China, this paper adopts the literature research method to study the development of secondary vocational education in China. Firstly, we searched the literature of secondary vocational education research and found that the main research literature was focused on three areas: "research on secondary vocational education development", "research on school-enterprise cooperation and industry-education integration model of secondary vocational education", and "research on secondary vocational teaching reform". After analyzing the hotspots of secondary vocational education research, the future directions that researchers should focus on in the field of secondary education research in the future are generally "problems in the development of secondary vocational education", such as promoting the research of "school-enterprise cooperation and integration of industry-education" in secondary vocational schools. "The important role of secondary vocational education as a bridge", such as the promotion of the "double high" policy, which opens up new channels for higher education or vocational-technical universities through the creation of specialties. "Teacher training and pedagogical innovation in secondary vocational education" e.g. interdisciplinary cross-fertilization. It is strongly believed that these recommendations will be useful for researchers concerned with the field of secondary vocational education